2013
DOI: 10.2174/15665240113139990021
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insight into the Inflammatory and Cellular Responses Following Experimental Glaucoma Surgery: A Roadmap for Inhibiting Fibrosis

Abstract: Failure after glaucoma filtration surgery is attributed to fibrosis at the operated site. To understand the wound healing process after glaucoma filtration surgery, we have developed a mouse model for glaucoma filtration surgery which closely mimics the clinical response. In this study, we describe a systematic analysis of the wound healing response in vivo. Our data revealed that the post-surgical tissue response was separable into two distinguishable phases. The early "acute inflammatory" phase was character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 0 publications
1
68
0
Order By: Relevance
“…The development of a mouse model of GFS (Seet et al, 2010) enables a quantitative assessment of fibrotic development through molecular analyses (Seet et al, 2013). This mouse model responded to mitomycin C (MMC), a commonly applied adjunctive antifibrotic therapy in clinical GFS, in a similar manner to that observed in patients (Seet et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of a mouse model of GFS (Seet et al, 2010) enables a quantitative assessment of fibrotic development through molecular analyses (Seet et al, 2013). This mouse model responded to mitomycin C (MMC), a commonly applied adjunctive antifibrotic therapy in clinical GFS, in a similar manner to that observed in patients (Seet et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This mouse model responded to mitomycin C (MMC), a commonly applied adjunctive antifibrotic therapy in clinical GFS, in a similar manner to that observed in patients (Seet et al, 2011). The fibrotic phase in this mouse model, which is measurable on day 7 post-experimental surgery, is marked by increased expression of extracellular matrix genes, including type I collagen ( Col1a1 ) (Seet et al, 2013). Col1a1 expression, as a quantitative marker for conjunctival fibrosis, can be measured at both the mRNA and protein levels via real-time quantitative polymerase chain reaction (qPCR) and immunoblotting techniques in the mouse model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seet et al 99 developed a systematic spatio-temporal analysis of the phases in the wound healing response to glaucoma filtration surgery using a mouse model. They observed that this post-surgical tissue response can be separated into two distinctive phases.…”
Section: Angiogenesis In the Medical Management Of Glaucomamentioning
confidence: 99%
“…119 Among different VEGF isotopes, VEGF-A is the only one showing significantly decreased expression in later stages of wound healing. 99 This suggests that VEGF-A may be involved in the transition from the early to late phases of wound healing. Among the different isoforms of VEGF-A, VEGF-121, VEGF-165, and VEGF-189 are expressed in rabbit Tenon fibroblasts.…”
Section: Therapy In Glaucoma Filtration Surgerymentioning
confidence: 99%